Свод Хаммурапи - Абдуллаев Чингиз Акифович (Современный русский шпионский роман, 2008)
Экземпляры: оиф (04.09.09) / Инвентарный номер: 43943 / Цена: 55.00 / Авт.знак: А 13 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44